National characteristics of preclinical studies and use of laboratory animals in Russia: problems and prospects - A. N. Murashev; V. S. Popov; M. S. Krasilshchikova; T. Yu. Zharmukhamedova; D. I. Rzhevskiy; O. N. Khokhlova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The analysis of the international experience in conducting preclinical studies and application of the principle of good laboratory practice was made. The issues associated with the use of laboratory animals for scientific purposes in Russia and abroad were discussed. The prospects of improvement of legislative base of the Russian Federation in the field of preclinical studies with the application of the principle of good laboratory practice and use of laboratory animals for scientific purposes were identified.